Transdermal patches: Design and current approaches to painless drug delivery - Al Hanbali Othman A.; Khan Haji Muhammad Shoaib; Sarfraz Muhammad; Arafat Mosab; Ijaz Shakeel; Hameed Abdul (Acta Pharmaceutica)
Use of transdermal patches can evade many issues associated with oral drug delivery, such as first-pass hepatic metabolism, enzymatic digestion attack, drug hydrolysis and degradation in acidic media, drug fluctuations, and gastrointestinal irritation. This article reviews various transdermal patches available in the market, types, structural components, polymer role, and the required assessment tools. Although transdermal patches have medical applications for smoking cessation, pain relief, osteoporosis, contraception, motion sickness, angina pectoris, and cardiac disorders, advances in formulation development are ongoing to make transdermal patches capable of delivering more challenging drugs. Transdermal patches can be tailored and developed according to the physicochemical properties of active and inactive components, and applicability for long-term use. Therefore, a number of chemical approaches and physical techniques for transdermal patch development are under investigation.